Germline genetics of cancer of unknown primary (CUP) and its specific subtypes - Hemminki, Kari; Chen, Bowang; Kumar, Abhishek; Melander, Olle; Manjer, Jonas; Hallmans, Göran; Pettersson-Kymmer, Ulrika; Ohlsson, Claes; Folprecht, Gunnar; Löffler, Harald; Krämer, Alwin; Försti, Asta (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.7903 Kari Hemminki, Bowang Chen, Abhishek Kumar, Olle Melander, Jonas Manjer, Göran Hallmans, Ulrika Pettersson-Kymmer, Claes Ohlsson, Gunnar Folprecht, Harald...